PERKEMBANGAN EMOSI PADA ANAK SEKOLAH DASAR DI UPT SDN 060876 - Nasution, Ayyu Rizkia; Atthoyibah, Assyifa'u Qolbiatu; Nasution, Dhea Syah Nazwa; Firmansyah, Ibnu; Tampubolon, M. Rizky Fauzan; Siregar, Sania (Universitas Negeri Medan, 2023)
The aim of this research is to determine the emotional development of students education at SDN 060876. This research method uses descriptive qualitative. The instruments used in this research were interviews and questionnaires. Study This is aimed at grade 5 students at SDN 060876. At SDN 060876, learning uses lectures and questionnaire instruments. Based on this research, the results of interviews and questionnaires show that Students' emotional development is influenced by the surrounding environment, namely the family environment, school environment and community environment. The conclusion of this research is Student emotional development can significantly influence student learning outcomes depending on each individual student and the surrounding environment. Keywords: Emotional development, SDN 060876, Children.